1973
DOI: 10.1111/j.1476-5381.1973.tb08219.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term treatment with high doses of guanethidine on sperm transport and fertility of rats

Abstract: Summary Male rats treated with guanethidine 25 mg/kg daily for eight weeks had no demonstrable ejaculatory function immediately after cessation of treatment. Four weeks later, ejaculatory function had returned in two‐thirds of the males, and after eight weeks, all males were able to deposit sperm in the vagina. However, fertility had returned at that time in only two of the nine males. On the basis of these findings it might be expected that fertility would return in the other males after a more prolonged obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…However, chronic treatment of rats with guanethidine (10 mg/kg) for 13 weeks has recently been shown not to decrease the number of axons nor to produce any degenerating axons in the vas deferens (Evans, Iwayama & Burnstock, 1973). Although these authors reported no restoration, after cessation of treatment, of contractile responses to stimulation previously blocked by guanethidine treatment, Hepp & Kreye (1973) did find that ejaculatory function was restored 8 weeks after guanethidine treatment had finished (25 mg/kg daily for 8 weeks). The latter result agrees with the findings in the present study where contractile responses were partly restored after cessation of guanethidine treatment.…”
Section: Discussionmentioning
confidence: 84%
“…However, chronic treatment of rats with guanethidine (10 mg/kg) for 13 weeks has recently been shown not to decrease the number of axons nor to produce any degenerating axons in the vas deferens (Evans, Iwayama & Burnstock, 1973). Although these authors reported no restoration, after cessation of treatment, of contractile responses to stimulation previously blocked by guanethidine treatment, Hepp & Kreye (1973) did find that ejaculatory function was restored 8 weeks after guanethidine treatment had finished (25 mg/kg daily for 8 weeks). The latter result agrees with the findings in the present study where contractile responses were partly restored after cessation of guanethidine treatment.…”
Section: Discussionmentioning
confidence: 84%
“…This is not the case concerning the smooth muscle of other organs, where the action of adrenergic and cholinergic fibers are opposed to each other. The fact that treated rats were able to ejaculate after mating (Hepp and Kreye -1973) or after electroejaculation, indicates that, although this obstruction cannot be avoided by an increased spontaneous activity, it can be overcome by the sudden contractions that take place during ejaculation. In our experiments the persistence of spontaneous motility in the ductus and the presence of spermatozoa in the ejaculate after electroejaculations, allows us to assume that cholinergic neurotransmission acts directly on the smooth muscle of the epididymis in absence of adrenergic innervation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested previously that regional variation along the length of the vas deferens of responsiveness to field stimulation and to noradrenaline may be of functional significance (Pennefather et al, 1974). Within the vas deferens, sperm are transferred in an epididymal to prostatic direction, and there is evidence to suggest that this transport is regulated by sympathetic activity both during and in between periods of sexual activity (Evans et al, 1972;Hepp & Kreye, 1973;Prins & Zaneveld, 1969;Zankl & Leidl, 1979 ; Alexander et a/., 1979). In the dog vas deferens hypogastric nerve stimulation in vivo produces a delayed co-ordinated contractile response which occurs first in the epididymal end and is followed 5-10 s later by contraction at the prostatic end of the tissue (Kimura ef ul., 1975).…”
Section: Discussionmentioning
confidence: 99%